Outcome Predictors of the Transforaminal Endoscopic Spine System Technique for Single-level Lumbar Disk Herniation - Wu, Jinchun; Yu, Bin; He, Bin; Liu, Gang; Ju, Jidong; Zhu, Jianguang (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2018)
Background Endoscopic spine surgery has become increasingly popular. However, no study has researched the predictive factors for different outcomes. This study is the first to evaluate the outcome predictors of the transforaminal endoscopic spine system (TESSYS) technique for lumbar disk herniation (LDH).Methods We performed a prospective study of 80 patients meeting the inclusion criteria who underwent TESSYS for LDH. Clinical outcomes were assessed by the visual analog scale (VAS), the Oswestry Disability Index (ODI), and the modified MacNab criteria. Univariate and multivariate analyses were performed to evaluate the outcome predictors.Results There were 36 men and 44 women with a mean age of 48.76 ± 15.60 years (range: 24–78 years). The mean follow-up time was 25.15 ± 9.76 months (range: 12–48 months). The VAS and ODI scores at the last follow-up were significantly improved (p < 0.001). Based on the modified MacNab criteria, the global outcomes were excellent in 34 patients (42.5%), good in 26 patients (32.5%), fair in 11 patients (13.75%), and poor in 9 patients (11.25%). The percentage of symptomatic improvement was 88.75%, and the success rate (excellent or good) was 75%. In the univariate and multivariate analyses, LDH with older age (odds ratio [OR]: 6.621; 95% confidence interval [CI], 0.632–20.846; p = 0.019), high-intensity zone (HIZ) (OR: 8.152; 95% CI, 0.827–4.380; p = 0.003), and larger disk herniation (OR: 6.819; 95% CI, 0.113–4.825; p = 0.017) were the most significant negative outcome predictors.Conclusions TESSYS is an effective method to treat LDH. Older age, the existence of an HIZ, and a large disk herniation were the most important predictors for a worse outcome.
Keywords: lumbar disk herniation; transforaminal endoscopic spine surgery; risk factor